A universal split spinach aptamer (USSA) for nucleic acid analysis and DNA computation. Issue 36 (20th April 2017) - Kikuchi, Nanami; Kolpashchikov, Dmitry M.
Abstract : A single universal spinach aptamer probe can be used to analyse potentially any nucleic acid sequences. Abstract : We demonstrate how a single universal spinach aptamer (USSA) probe can be used to detect multiple (potentially any) nucleic acid sequences. USSA can be used for cost-efficient and highly selective analysis of even folded DNA and RNA analytes, as well as for the readout of outputs of DNA logic circuits.